Pengaruh Aset Pajak Tangguhan, Kebijakan Deviden, Dan Tax Planning Terhadap Earnings Management - Nunung Komalasari; Adhitya Putri Pratiwi (CV. ITTC INDONESIA, 2024)
This study aims to analyze deferred tax assets, dividend policies and tax planning on earnings management. This research was conducted by analyzing the financial statements of companies in the consumer cyclicals sector listed on the Indonesia Stock Exchange (IDX) during the period from 2018 to 2022. The sample used in this study was 9 companies in the consumer cyclicals sector listed on the Indonesia Stock Exchange during the period from 2018 to 2022 using purposive sampling techniques. The data used in this study is secondary data in the form of financial statements from each company that has been used as a research sample. The variables used in this study are Deferred Tax Assets (X1) as the first independent variable, Dividend Policy (X2) as the second independent variable, and Tax Planning as the third independent variable and Earnings Management (Y) as the bound variable. The panel data regression method is used as the research methodology in this study. The analysis of the research results was carried out using the help of EViews 12 Student Version Lite software.The results of this study show that Deferred Tax Assets partially did not have any effect on Earnings Management, Dividend Policy partially did not have any effect on Earnings Management, and Tax Planning partially affects Earnings Mnagement, and simultaneously Deferred Tax Assets, Dividend Policy and Tax Planning have an effect on Earnings Management.